2022
DOI: 10.1002/iid3.690
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3‐dioxygenase gene expression and kynurenine to tryptophan ratio correlation with nasopharyngeal carcinoma progression and survival

Abstract: Introduction Indoleamine 2,3‐dioxygenase (IDO) is an immunosuppressive tryptophan‐depleting enzyme expressed in nasopharyngeal carcinoma (NPC) tissue. However, IDO has not been reported in the peripheral blood of NPC patients. The aim of this study was to analyze, IDO1 and IDO2 messenger RNA (mRNA) expression, the kynurenine (Kyn) and tryptophan (Trp) plasma levels, their clinical values and their relationship with cytokine levels in NPC. Methods We evaluated IDO1 and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Many studies have focused on the imbalances in tryptophan metabolism by targeting the KP, especially ryptophan-2,3-dioxygenase (TDO), indoleamine-2,3,-dioxygenase 1 (IDO1), and IDO2 ( Platten et al, 2019 ; Yao et al, 2021 ). It has been demonstrated that the tryptophan depletion by IDO1 and IDO2 was highly associated with cellular function and survival ( Zhai et al, 2018 ; Souissi et al, 2022 ). However, phase III clinical trials of IDO inhibitors against cancers were disappointing, although they did show promising outcome in early-stage cancer immunotherapy ( Günther et al, 2019 ; Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on the imbalances in tryptophan metabolism by targeting the KP, especially ryptophan-2,3-dioxygenase (TDO), indoleamine-2,3,-dioxygenase 1 (IDO1), and IDO2 ( Platten et al, 2019 ; Yao et al, 2021 ). It has been demonstrated that the tryptophan depletion by IDO1 and IDO2 was highly associated with cellular function and survival ( Zhai et al, 2018 ; Souissi et al, 2022 ). However, phase III clinical trials of IDO inhibitors against cancers were disappointing, although they did show promising outcome in early-stage cancer immunotherapy ( Günther et al, 2019 ; Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the STAT3/IL-6 axis is assumed to regulate the constitutive expression of IDO1 in tumor cells ( 16 ), leading to the hypothesis that this axis could regulate the high-level expression of IDO1 in the tumor microenvironment and adjacent tissues of HPV-related tumors ( 27 , 45 48 ), since both molecules are co-expressed in TC-1 cell mouse model or cervical cancer patients. Indeed, IL-6 and IDO have been linked to poor treatment outcomes, tumor recurrence, and aggressive tumor progression in breast cancer ( 49 ), nasopharyngeal carcinoma ( 50 ), and prostate cancer ( 51 ) patients. Therefore, the study of these two immunosuppressive molecules is important not only for HPV-related tumor, but also for other tumor types.…”
Section: Discussionmentioning
confidence: 99%